Management of Meunasah: Empowering The Religiosity of School-Age Children through Non-Formal Education - Almuhajir, Almuhajir (JURNAL AL-TANZIM, 2023)
This study aims to explain the management of the meunasah in empowering the religiosity of school-age children through non-formal education in Lhokseumawe City. This study uses a qualitative approach. Data sources and data collection techniques were obtained from interviews, observations, and documentation. Data analysis techniques include data reduction, display, and verification. The results of the study show that there are three interrelated aspects in empowering religiosity through meunasah, namely: 1) Aspects of aneuk miet beuët, consisting of an analysis of the needs of aneuk miet beuët, recruitment and selection at the beginning of each learning year, grouping and development in learning, as well as reporting on the progress of each end of semester, 2) Teungku Aspect, consisting of recruitment carried out by Qur'an recitation coaches with a direct test system for Qur'an abilities, Islamic insights, and interviews/psychotests, placement according to competence and compensation according to performance, and evaluation is carried out through interviews and observation in non-formal situations, 3) Curriculum Aspect, consisting of the learning curriculum at the meunasah which is the result of a teacher's deliberation agreement, the subject matter taught is the Qur'an, Fiqh worship, memorizing prayers, and Arabic, visual learning media and audiovisual with halaqah, memorization, and drill methods, as well as an evaluation system consisting of pre-test, post-test, and summative tests.